A novel spinel-type Mg0.55Al2.36O3.81N0.19 transparent ceramic with infrared transmittance range comparable to c-plane sapphire. (15th March 2020) - Zong, Xiao; Wang, Hao; Gu, Honggang; Ren, Lu; Tu, Bingtian; Wang, Weimin; Liu, Shiyuan; Fu, Zhengyi
Abstract: A novel Mg0.55 Al2.36 O3.81 N0.19 transparent ceramic with an infrared transmission range comparable to c-plane sapphire was prepared based on the intentional design of the composition. This material possesses outstanding optical properties, such as a high in-line transmittance up to 86.5% at 3.7 µm, a refractive index of 1.7240 at 589.3 nm and an absorption coefficient of 0.8 cm −1 at 5 µm. The effects of chemical composition on the crystal structure and optical properties of spinel material were discussed. In particular, the chemical bond strength of disordered tetrahedron varying with the composition largely determines the infrared transparent range of transparent ceramic. Graphical abstract: Image, graphical abstract